Studi Independen Bersertifikat Data Analytics di Zenius Education - Azis, Muas Abdul; Pusvikasari, Nila; Deitiana, Tita; Soediono, Wibisono (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The final report of this independent study program is shown to explain the author's activities while participating in the Free Learning - Independent Campus (MBKM) activities which are a government program that aims to improve the abilities and expertise of students organized by the Ministry of Education and Culture. This report contains the author's activities while participating in independent Data Analytics study activities at PT Zona Edukasi Nusantara (Zenius Education). The things explained include Fundamental Thinking learning activities then followed by Data Analytics learning which ends with giving final assignments in groups by analyzing Home Credit's company data needed by company stakeholders in making decisions. Even though there are still limitations that still need to be improved, this program contributes to society.